2019
DOI: 10.37358/rc.19.6.7247
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Biological Total Phosphorus Removal Process

Abstract: This article investigates the efficiency of phosphorus removal in the municipal wastewater treatment plants in five counties of Romania from 2013 to 2017. This study focused on evaluation of the performance of phosphorus elimination using biological methods in order to respect the admissible effluent discharge limits. The yearly average of inflow total phosphorus varies from 3.64 mg/L to 4.22 mg/L comparing with 1.02 mg/ L and 1.59 mg/L the average of outflow. Chemical and biological methods are utilized to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…On the other hand, human activities result in significant wastewater amounts-both domestic and industrial. Domestic wastewaters contain organic pollutants, nitrogen compounds-ammonium [7], phosphorus compounds from detergents and products for water softening [8,9], as well as microplastics [10,11], which are hardly biodegradable [12,13]. The majority of industrial wastewater comes from diverse areas, such as tannery [14,15], mining [16], pharmaceuticals [17,18], the food industry [19,20], the textile industry [21][22][23], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, human activities result in significant wastewater amounts-both domestic and industrial. Domestic wastewaters contain organic pollutants, nitrogen compounds-ammonium [7], phosphorus compounds from detergents and products for water softening [8,9], as well as microplastics [10,11], which are hardly biodegradable [12,13]. The majority of industrial wastewater comes from diverse areas, such as tannery [14,15], mining [16], pharmaceuticals [17,18], the food industry [19,20], the textile industry [21][22][23], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of surface water and groundwater [24][25][26][27][28] is largely determined by the organic pollutants content (such as petroleum products [29], xenobiotics [30,31], hardly biodegradable plastics [32,33], etc. ), inorganic pollutants (such as phosphates and polyphosphates [8,9], heavy metals [16,34,35], etc. ), biohazardous residues [36,37], etc., in discharged wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, large amounts of domestic wastewater are generated [18][19][20], with appreciable content of organic substances, phosphorus compounds (from detergents) [21], [22], nitrogen compounds [23], [24], including various species of bacteria [25].…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of sustainable development, the issue of conservation/reuse of natural resources is a priority. In this context, a very complex problem, with unique material and social implications, is that of municipal waste [2] solids with frequent content of plastics/polymers [3]- [8] (hardly biodegradable [9]- [13] and with persistent pollutant content [14]- [17]) and/or liquids, such as oils (hardly biodegradable [18]), domestic wastewaters with a wide range of pollutants such as heavy metals [18], phosphorus compounds [19], [20], nitrogen [21], [22], sulphur compounds [23], etc. It was found that the level of municipal wastewater pollution is directly related to the way of waste management in that locality [24], [25].…”
Section: Introductionmentioning
confidence: 99%